Comparing body condition and foraging ecology of two populations of Cape Gannets on Bird and Malgas Islands - Moseley, Christina (Percy FitzPatrick Institute of African Ornithology, 2014)
Cape gannets (Morus capensis) are one of the dominant seabirds in the Benguela current ecosystem and feed mainly on sardines (Sardinops sagax) and anchovy (Engraulis encrasicolus). Starting in the late 1990s the distribution of these fish shifted from the west coast of South Africa to the south-east coast. This has resulted in gannets on the west coast feeding extensively on fishery wastes, which slows the growth of chicks and decreases their fledging mass. I compared the foraging ecology, diet and body condition of adult Cape gannets from two colonies, one where individuals have been feeding on fishery wastes (hake) for several years (Malgas Island; west coast) and the other where individuals feed on natural prey (Bird Island; south coast). In October and November 2009, through the use of GPS loggers I compared the foraging behaviour of birds from the two colonies. I compared the diet of gannets at the two colonies, using stomach contents samples and an isotopic mixing model using stable isotope ratios of carbon and nitrogen in blood, feathers and potential prey. I also compared the body condition of adults by measuring pectoral muscle thickness and other morphological parameters. These results were analysed with data from a concurrent hydro-acoustic survey of the distribution and abundance of pelagic fish along the coast of South Africa. The hydro-acoustic survey showed that more than half of the sardine and anchovy stocks were present on the west coast for the first time in several years but that the overall biomass of these two species remained low in the southern Benguela. Stomach samples and isotopic analysis of blood showed that gannets at both colonies fed mainly on sardines during the study period. Long-term diet estimates from feather isotopes suggest that there was little hake in the diet of birds at Malgas Island, despite the direct diet samples showing that hake and saury dominated the diet over the preceding 10 months. This could be due to insufficient prey sampling or the diet samples not being representative of the gannet population as a whole. Gannets from Bird Island made longer foraging trips and flew further from their colony than did those from Malgas Island. Individuals from this colony had slightly greater pectoral muscle thicknesses and body masses (after controlling for size) than those from Bird Island, but 4 this was not significant. Despite gannets from Malgas Island relying on fishery wastes for a number of years, there has been little effect on body condition among breeding birds when compared with Bird Island gannets feeding on pelagic fish. Two possible reasons for this are that (1) when feeding on fishery wastes, adults decrease their reproductive effort to preserve body condition or (2) gannets on the west coast have regained body mass and pectoral muscle rapidly since the local recovery of sardines. It is likely that the gannets from Bird Island have greater foraging costs due to intra-specific competition for food as the colony has increased five-fold in size over the last 50 years. However, chick growth and adult body condition have been affected only marginally. Despite the presence of sardine and anchovy on the west coast, it is likely that Cape gannets are food limited, especially since there is also a strong spatio-temporal overlap of gannet foraging with the large commercial purse-seine fishery. Better spatial management of this fishery is necessary to ensure the persistence of seabirds and other top predators in the southern Benguela.